Impaired sensitivity to thyroid hormones is associated with hyperuricemia in a Chinese euthyroid population - Lu, Yingning; Wang, Jie; An, Yu; Liu, Jia; Wang, Ying; Wang, Guang; Leng, Song (Frontiers in Endocrinology, 2023)
Objective Impaired sensitivity to thyroid hormones has been reported as a common metabolic disorder, and it remains poorly understood whether it interplays with uric acid (UA) metabolism as an established risk factor for cardiovascular diseases (CVDs). We aimed to investigate the relationship between thyroid hormone sensitivity and elevated UA in a Chinese euthyroid population. Methods A total of 15,955 euthyroid subjects were included in this study. Thyroid hormone sensitivity indices were calculated, including the thyroid feedback quantile-based index (TFQI), the Chinese-referenced parametric TFQI (PTFQI), the TSH index (TSHI), and the thyrotropin thyroxine resistance index (TT4RI), and the FT3/FT4 ratio. Linear and logistic regression analyses were performed to detect the association between thyroid hormone sensitivity and elevated UA. Results Subjects with reduced sensitivity to thyroid hormones had increased UA levels in both genders (p for trend < 0.001). Logistic and linear regression analyses showed that higher TFQI, PTFQI, TSHI, and TT4RI were positively associated with elevated UA levels, but negatively associated with the FT3/FT4 ratio. The odds ratio (OR) of the highest versus the first quartile of TFQI was 1.20 (1.05, 1.38) in men and 1.80 (1.46, 2.23) in women (p < 0.001). PTHQI, TSHI, and TT4RI obtained similar results in both genders. Conversely, the highest quartile of the FT3/FT4 ratio was negatively correlated with elevated UA levels [men: OR 0.78 (0.68,0.89), women: OR 0.66 (0.53,0.81)]. Conclusion Impaired sensitivity to thyroid hormones was associated with elevated UA levels in euthyroid subjects. Our findings shed light on the role of thyroid hormone sensitivity in UA metabolism.